Molecular characterization of infectious bursal disease virus isolated in Chile reveals several mutations in VP2 coding region and a reassortment in its genome - Guzmán, Miguel; Cádiz, Leandro; Guerrero Moncayo, Alejandra.; Cáceres, Francisca; Vidal, Sonia; Lapierre, Lisette; Sáenz, Leonardo; Hidalgo, Héctor (My University, 2022)
Infectious Bursal Disease (IBD) is a well-described disease in young chickens. It is caused by the Infectious Bursal Disease Virus (IBDV), which has a bi-segmented, double-strand RNA genome. The absence of a lipidic envelope makes IBDV highly resistant to environmental conditions. Consequently, it is widely reported around the world. Fourteen samples retrieved from chickens exhibiting apparent alterations of the bursa of Fabricius between 2017 and 2021 were included in the study. These samples were passaged into embryonated eggs and the presence of IBD was confirmed through RT-PCR. The PCR products were sequenced and analyzed to characterize the Chilean IBDV isolates for comparison with GenBank sequences, including vaccines sequences currently used in Chile. Phylogenetic analysis classified the Chilean sequences as A1B1, except the sample 15002_CL_2021 which was classified as A2B1. On the other hand, all Chilean viruses were grouped as B1, based on viral segment B. Estimated evolutionary divergence between different genogroups supports these clustering. Moreover, samples 13936_CL_2017, 14038_CL_2017, 14083_CL_2017, 14145_CL_2018, 14431_CL_2019, and 14459_CL_2019 showed high similitude with the D78 and ViBursa CE vaccines (both currently used in Chile). Viruses 14010_CL_2018, 14040_CL_2017, 14514_CL_2019 and 14019_CL_2017 exhibited patterns that do not exactly fit either vaccine. Finally, viruses 15,041 N-_CL_2021, 15,041 N+_CL_2021, and 15004_CL_2021 showed even more differences regarding both vaccines. This is the first study in Chile to analyze the genetic sequences of IBDV isolates. The different assessments conducted as part of the study suggest a close relationship with vaccines currently in use. Interestingly, one of the viruses exhibited a reassortment in its genome segments, which could confer new characteristics to the virus. However, new approaches would be required to establish the origin of the isolated viruses, as well as how the recombination is changing its virulence or morbidity.
Keywords: Animales; Infecciones por birnaviridae; Pollos; Aves de corral - Enfermedades; Infectious bursal disease virus